Design, fabrication and characterization of silicon nanowire-based DNA biosensor for dengue virus DNA detection - Abd Rahman, Siti Fatimah (2016)
Silicon nanowire (SiNW) has attracted significant interest because of its potential applications from nanoscale electronics to biomedical engineering. The SiNW represent an important class of materials with unique features such as identical diameters to biomolecules, applicable to apply in biomolecule or chemical detection and can be fabricated as highly sensitive biosensor device. Thus, this study demonstrates the development of SiNW biosensor for detecting deoxyribonucleic acid (DNA) of dengue virus utilizing electron beam lithography (EBL) coupled with conventional lithography (CL) for device fabrication. The surface of fabricated SiNW is chemically modified using 3-aminopropyltrieloxysilane (APTES) in order to transform the devices as a functional sensing element. Prior to biomolecule testing, the amine-terminated SiNW device is first evaluated in response to the pH level detection for optimizing the sensor sensitivity that related to the effect of SiNW width and SiNW number. It was found that, the device consist of single SiNW with 60 nm in width shows the highest sensitivity as compared to those devices consists of larger SiNW and in array formation as well. The optimized SiNW device is then employed for the detection of dengue virus DNA by introduced the additional of three-step procedure involving glutaraldehyde surface treatment, DNA immobilization and DNA hybridization. Contact angle measurement, fourier transform infrared spectroscopy (FTIR) and x-ray photoelectron spectrometry (XPS) are used to assess the effectiveness of the attachment protocol. The detection principle works by detecting the changes in the electrical current of SiNW which bridge the source and drain terminal to sense the immobilization of probe DNA and their hybridization with target DNA. The oxygen (O2) plasma is proposed as an effective strategy for increasing the binding amounts of target DNA by modified the SiNW surface. It was found that the detection limit of the 60 sec plasma treated-SiNW device could be reduce to 1.985 x 10-14 M as compared to 4.131 x 10-13 M for the untreated-SiNW device with a linear detection range from 1.0 x 10-9 M to 1.0 x 10-13 M of complementary target DNA. In addition, the developed biosensor device was able to discriminate between complementary, single mismatch and non-complementary DNA sequences. This highly sensitive assay is also able to detect reverse transcription-polymerase chain reaction (RT-PCR) product of dengue virus DNA in real samples, making it as a potential method for disease diagnosis through electrical biosensor detection.